First High-Frequency Underway Observation of DMS Distribution in the Southern Ocean during Austral Autumn - Intae Kim; Miming Zhang; Kitae Kim; Keyhong Park (Atmosphere, 2021)
We investigate the distribution of dimethyl sulfide (DMS) in the Southern Ocean’s (50° W to 170° W) surface water, including the Antarctic Peninsula and the marginal sea ice zone (MIZ) in the Ross and Amundsen Seas. This is the first high-frequency observation conducted in the austral autumn (in April) in the Southern Ocean. The mean DMS concentration was 2.7 ± 2.5 nM (1 σ) for the entire study area. Noticeably enhanced DMS (5 to 28 nM) concentrations were observed in the MIZ around the Ross and Amundsen Seas and the coastal regions in the Antarctic Peninsula; this could be attributed to biological production of local ice algae, which appears to be supplied with nutrients from glacial or sea ice melt water. These observed DMS inventories were significantly higher (an order of magnitude) than current climatological DMS inventories. The local DMS sources being transported outward from the polynyas, where strong bloom occurs during summer, could result in larger discrepancies between observed DMS and climatological DMS in the MIZ area (in the Amundsen Sea). Overall, this study is the first to highlight the significance of the underestimation of current DMS fluxes in the austral autumn, which consequently results in significant errors in the climate models.